2022
DOI: 10.1093/bjsw/bcac204
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Separation: Learning from Those with Former Foster Care Experiences

Abstract: Sibling relationships of youth in foster care are often complicated as many youth are separated from their sibling(s) at one point or another. Quantitative studies have identified ways in which sibling placement influences youth outcomes. Fewer qualitative studies have been conducted to understand youth perspectives about their sibling relationships. The purpose of this qualitative study was to examine sibling relationships and sibling separation amongst adults with prior foster care experience. Thematic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yet, most youth in this study reported wanting more sibling contact than they had. Relatedly, findings from a qualitative investigation of sibling relationships of those with former foster care experience indicated that participants believed more could have been done to promote their sibling relationships (Wojciak et al, 2022). Taken together, findings may suggest that sibling relationships may be an underappreciated resource for youth in foster care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, most youth in this study reported wanting more sibling contact than they had. Relatedly, findings from a qualitative investigation of sibling relationships of those with former foster care experience indicated that participants believed more could have been done to promote their sibling relationships (Wojciak et al, 2022). Taken together, findings may suggest that sibling relationships may be an underappreciated resource for youth in foster care.…”
Section: Discussionmentioning
confidence: 99%
“…While scholars have designed interventions specifically for sibling relationships, there also are practical things those involved with the child welfare system can do to facilitate sibling relationship quality. Specifically, a study of former foster youth indicated that members of the child welfare system should take advantage of technological advancements, such as social media, when siblings cannot be placed together (Wojciak et al, 2022). Participants also indicated that greater efforts can be made to ensure that youth receive their siblings’ new contact information, and that more intentional efforts be made to ensure youth have transportation to see one another.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the impacts of child apprehension on families primarily focuses on the experiences of separation between mothers and their children and between siblings (Font & Kim, 2022; Thumath et al, 2021; Wojciak et al, 2023). Child apprehension has been found to have devastating and life-threatening impacts on mothers such as an increased likelihood of suicide attempts and mental health related hospitalizations (Thumath et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has also demonstrated that there are detrimental impacts to siblings who are separated in OOHC, and yet they are often not placed together (Leathers, 2005; Schwenke et al, 2006). Sibling separation has been associated with strained sibling relationships, long-term mental health impacts, increased risk of criminal behavior, and lower school achievement (Novak & Benedini, 2020; Wojciak et al, 2023). While there is currently an absence of literature focused specifically on Black sibling relationships in care, Font and Kim (2022) argue that sibling separation may have unique impacts on Black youth given they are more likely to stay in OOHC longer and be placed in transracial placements that do not meet their cultural needs.…”
Section: Literature Reviewmentioning
confidence: 99%